2021
DOI: 10.1007/s00391-021-01900-z
|View full text |Cite
|
Sign up to set email alerts
|

Gewichtsverluste und Mangelernährungsrisiko bei geriatrischen PatientInnen

Abstract: Zusammenfassung Hintergrund Mangelernährung stellt eine große Herausforderung im klinischen Alltag dar und ist mit einer erhöhten Mortalität assoziiert. Ziel der Arbeit Im vom Bundesministerium für Bildung und Forschung (BMBF) geförderten Forschungsprojekt Prävention und Behandlung von Mangelernährung bei geriatrischen Patienten im Krankenhaus werden Routinedaten ausgewertet. Ziel ist es, die Ursachen eines in der Klinik erworbenen Mangelernä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Neelemaat et al compared five MSTs for patients in one hospital and found that 47% of the data were missing for MUST and 41% were missing for MNA-SF [10]. They also reported that MUST had low applicability due to the high rate of missing data, while the MNA-SF showed excellent sensitivity but low specificity.…”
Section: Deficiencies In Nutrition Screening Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Neelemaat et al compared five MSTs for patients in one hospital and found that 47% of the data were missing for MUST and 41% were missing for MNA-SF [10]. They also reported that MUST had low applicability due to the high rate of missing data, while the MNA-SF showed excellent sensitivity but low specificity.…”
Section: Deficiencies In Nutrition Screening Parametersmentioning
confidence: 99%
“…However, in hospitals, nursing homes, and communities, bodyweight, which is required for evaluating nutritional parameters such as low BMI and unintentional weight loss, is often not measured [10][11][12]. This has led to the inadequate nutritional screening of patients and the elderly and has caused cases of malnutrition to be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Sowohl die in früheren Datenauswertungen [24] als auch die in dieser Stichprobe selten durchgeführten Mangelernährungsscreenings verweisen auf eine nicht optimale Umsetzung des in den Einrichtungen implementierten Expertenstandards. Zwar wird sehr zuverlässig monatlich gewogen, jedoch das eigentlich notwendige regelmäßige Screening [20] eher vernachlässigt.…”
Section: Prävention Und Versorgungsqualitätunclassified